Maternal Vitamin D Status Affects Hepatitis B Vaccine Response in Breastfeeding Infants. (29th May 2020) - Newton, Danforth; Baatz, John; Shary, Judy; Washington, Renee; Wagner, Carol
Abstract: Objectives: Vitamin D (VitD) affects immune function across the lifespan, which includes pregnancy and lactation. We hypothesized that the response of fully breastfeeding (BrF) infants to HBV would differ as a function of maternal and/or infant's vitD status as measured by circulating 25-hydroxyD (25-D) concentration. Methods: Plasma 25-D concentration and HBV titers were measured in a subset of mothers and exclusively BrF infants ( n  = 56 pairs) participating in a lactation vitD supplementation clinical trial. Mothers were randomized to receive either 400 vs. 6400 IU vitD3 /day and infants 400 IU/day or placebo (if mother was in 6400 IU group). An additional 14 infants were exclusively formula-fed (FF). 25-D concentration (RIA) and infant anti-HBV IgG titers (ELISA) after 3 vaccinations (7 months of age) were measured. The associations between maternal vitD treatment group, circulating 25-D, and HBV IgG titers were explored using t-tests, ANOVA and linear correlations. Results: After 3 vaccinations, all infants in this study were considered to be highly immune to HBV (plasma anti-HBV surface IgG titer >100 IU/mL). However, we found that mean anti-HBV IgG titers in exclusively BrF infants were significantly lower if mother was vitD sufficient (2200 vs 4500 IU/ml; P  = 0.017), with inverse correlation between infant IgG titers and maternal vitD status ( r = −0.31; P  = 0.02). We also found that these infant anti-HBV titers were not significantly correlated with their own vitD status ( P  = 0.18). Results also showed that mean titers in exclusively FF infants were not correlated with vitD status and were nearly identical to those of BrF infants of vitD-insufficient mothers. Conclusions: Though still considered immune after 3 vaccinations, HBV IgG titers of BrF infants differed at 7 months of age by maternal vitD treatment and not on the basis of infant vitD status. These findings suggest that effects of vitD on breastmilk composition results in regulation of an infant's immune response perhaps by induction of immunotolerance, whether through blunting of a massive immune response to HBV antigens or affecting a more rapid switch from active plasma cells to memory B cells. A currently ongoing lactation pilot study continues to collect samples to confirm and expand these findings. Funding Sources: NIH/NCATS, SC Translational Research Institute, MUSC Pediatrics.